PENYEBAB KETERLAMBATAN KEGIATAN PENGADAAN IMPOR BARANG LOGISTIK HIGH DAMPING RUBBER BEARING - MARTHALEINA RS; YAYUK DWI INDRIANI (Institut Transportasi dan Logistik Trisakti, 2015)
PT. Wijaya Karya (Persero) Tbk is a construction company that has 6 subsidiaries and 10 operating departments. In conducting its business, the company is applying sourcing materials locally and internationally. One of them is the procurement of goods imported High Damping Rubber Bearings (HDRB) that serves as the foundation of anti-earthquake building structures and cannot be produced inside the country. Using a causal diagram (fishbone diagram; Dr. Kaoru Ishikawa), it was found that the factors causing delays in goods (HDRB) is due to production machinery, human resources, time, method, and money.